Precession Intuitively Explained - Hantz, Péter; Lázár, Zsolt I. (Frontiers in Physics, 2019)
Formal explanations of the dynamics of free and heavy tops are considered to be known for centuries. However, intuitive understanding of their unexpected behavior is still a challenge. In this paper, we present elementary force based explanations of several phenomena related the dynamics of heavy symmetric tops, derived in inertial and non-inertial reference frames. Simple calculations are enabled by a model equivalent to a spinning top, namely a square-formed tube carrying a streaming ideal fluid or a frictionless chain. Precession in a combined, gravitational and magnetic field is also discussed.